Financial Constraints in Mining Companies: Green Innovation and Ownership Structure Does Matter? - Yuyun Isbanah; Refiana Dwi Maghfiroh; Nadia Asandimitra; Trias Madanika Kusumaningrum (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
This study aims to analyze the effect of green innovation and ownership structure on green innovation. The ownership structure is proxied by managerial ownership and institutional ownership. The type of data used is secondary data from the Indonesia Stock Exchange in 2018 - 2021. The population of this study are companies listed on the Indonesia Stock Exchange. The sampling technique used purposive sampling with the following criteria: mining sector companies and non-state-owned companies. State-owned companies were excluded from the sample because state-owned companies if they experience funding difficulties, will generally be given an injection of funds from the government. The dependent variable is corporate financial constraints. The independent variables are green innovation, managerial ownership, and institutional ownership. The results show that green innovation and institutional ownership positively affect financial constraints, while managerial ownership negatively affects financial constraints. The managerial implication of this research is that in the short term, the implementation of green innovation for companies increases financing constrain because companies need funds to finance the implementation of green innovation.